The Nexus Between Organisational Justice, Job Satisfaction, and Organisational Citizenship Behaviour: The Case of Barclays Bank - Ocra, Ben T. (Advances in Social Sciences Research Journal, 2021)
This study examined the nexus between organisational justice, OCB, and job satisfaction. It also attempted to control for relevant covariates to contribute to the literature. The study was a correlational design, and its population was employees at the head office of Barclays Bank Ghana Limited (BBGL). All two hundred and seven (207) employees who met some selection criteria participated in the study. A self-administered questionnaire was used to collect data. Data was analysed using SPSS (Statistical Package for the Social Sciences). Descriptive statistics, Pearson’s correlation test, and Structural Equation Modelling (SEM) were used to present findings of the study. Organisational justice made a positive effect on job satisfaction and organisational citizenship behaviour. Job satisfaction also made a significant positive effect on organisational citizenship behaviour. It is concluded that increasing the level of justice delivered can improve the level of job satisfaction and organisational citizenship behaviour.